G594 An intercalated bsc in paediatrics and child health: improving the profile of paediatric training in medical school undergraduates. (May 2019) - King, JA; Fitchett, EJ; Winyard, P; Fertleman, C
Abstract : Aims: Often referred to as the 'last of the true general specialties, ' almost half of medical student entrants express an interest in paediatrics as a future career. However the profession is facing significant challenges in recruitment, with first round applications to postgraduate training falling from 800 to 580 between 2015 and 2017, leaving an unprecedented 17% of places unfilled. Here we examine using a BSc in paediatrics and child health to improve the profile of paediatric training in medical school undergraduates. Methods: In 2010 our institution developed the world's first intercalated BSc in Paediatrics and Child Health to help widen understanding of child health and children's health services at an undergraduate level. In order to examine the impact of our BSc we used a logistic regression model to examine the effect of the BSc programme on final exam marks for our programme alumni. We examined the ranking of applications to paediatric training from our graduates before and after the initiation of the programme and explored feedback from programme alumni. Results: Strengths of the BSc include a strong clinical focus, independent learning and resilience in clinical environments, early clinical mentoring, independent development of research projects and a heavy focus on developing reflective practice as an essential skill for doctors in training. After adjusting for confounders, programme alumni obtained higher percentage points overall in their finals paper mark [1.96 (95% CI 0.31–3.62; p=0.02)] and in their finals objective structured clinical examination (OSCE) [2.51 (95% CI 1.22–3.80; p<0.0001)]. Percentage of our medical school graduates applying to paediatrics training has gone from second bottom to near the top amongst UK medical schools. Improved perception of Paediatrics as a competitive yet fulfilling career from our BSc has encouraged training applications throughout our medical school graduates, not just those who complete the BSc. Conclusions: A BSc programme in paediatrics and child health is an effective way to raise the profile of paediatric training amongst medical undergraduates in the UK and should be encouraged to increase training applications.